Correlations of perioperative coagulopathy, fluid infusion and blood transfusions with survival prognosis in endovascular aortic repair for ruptured abdominal aortic aneurysm. Issue 1 (December 2016) - Kawatani, Yohei; Nakamura, Yoshitsugu; Kurobe, Hirotsugu; Suda, Yuji; Hori, Takaki
Abstract Background Factors associated with survival prognosis among patients who undergo endovascular aortic repair (EVAR) for ruptured abdominal aortic aneurysms (rAAA) have not been sufficiently investigated. In the present study, we examined correlations between perioperative coagulopathy and 24-h and 30-day postoperative survival. Relationships between coagulopathy and the content of blood transfusions, volumes of crystalloid infusion and survival. Methods This was a retrospective study of the medical records of all patients who underwent EVAR for rAAA at Chiba-Nishi General Hospital during the period from October 2013 to December 2015. Major coagulopathy was defined using the international normalized ratio or activated partial thromboplastin time (APTT) ratio of at least 1.5, or platelet count less than 50 × 10/l. We quantified the amounts of blood transfusions and crystalloid infusions administered from arrival to the hospital to admission to ICU following operations. Results Coagulopathy among patients with rAAA was found to progress even after they had presented at the hospital. No statistically significant correlation between preoperative coagulopathy and mortality was found, although a significantly greater degree of postoperative coagulopathy was seen among patients who died both within 24-h and 30 days postoperatively. Among patients with postoperative coagulopathy, lesser quantities of fresh frozen plasma (FFP) compared with red cell concentrate (RCC) were used during the period from hospital arrival to postoperative ICU entry. In both groups of patients who did not survive after 24-h and 30 days, FFP was used less than RCC. Large transfusions of crystalloids administered during the periods from hospital arrival to surgery and from hospital arrival to the end of surgery were associated with postoperative incidence of major coagulopathy, death within 24-h, and death within 30 days. Conclusion Coagulopathy progressed during care in the emergency outpatient clinic and operations. Postoperative coagulopathy was associated with poorer outcomes. Smaller FFP/RCC ratios and larger volumes of crystalloid infusion were associated with development of coagulopathy and poorer prognosis of survival. Trial registration This study is retrospectively registered in UMIN Clinical Trials Registry (Registration 19 April 2016, registered number is R000025334UMIN000021978 ).